Monocyte‐predominant engraftment, cytokine levels and early transplant‐related complications in pediatric hematopoietic stem cell recipients. (28th January 2019) - Maximova, Natalia; Granzotto, Marilena; Barbieri, Francesca; Marcuzzi, Annalisa; Tommasini, Alberto; Monasta, Lorenzo; Simeone, Roberto; Zanon, Davide; Sala, Roberto
Abstract: Myeloablative conditioning is a well‐established procedure that precedes hematopoietic stem cell transplantation (HSCT), particularly in pediatric patients. In the period directly following transplantation, several factors may contribute to complications that lead to the activation or damage of endothelial cells, involved in the pathogenesis of vascular endothelial syndromes (VES). However, to date, sufficiently specific and sensitive diagnostic markers for the various forms of VES have not been identified. This was a retrospective single‐center study of patients who underwent allogeneic HSCT. For this cohort of patients, parameters including type of engraftment, donor characteristics, and cytokine production were measured and correlated with a high prevalence of short‐term complications after HSCT. The aim of this study was to identify specific parameters useful for improving diagnostics and predicting adverse effects in VES. We confirmed that monocyte‐predominant engraftment was related to a higher risk for an early transplant‐related complication termed sinusoidal obstruction syndrome (SOS). The increased production of specific cytokines, in particular RANTES, represents a marker associated with prevalent engraftment. In addition, patients undergoing prophylaxis with defibrotide had "classical" engraftment, a common cytokine profile and a lower incidence of life‐threatening transplant‐related complications. The beneficial effect of defibrotide might be a starting point for developing selective prophylaxis for patients with monocyte engraftment to prevent severe early transplant‐related complications. Abstract : The onset of vascular endothelial syndromes after hematopoietic stem cell transplantation is significantly associated with monocyte‐predominant engraftment ( P  < 0.0001). The increased production of specific cytokines, in particular RANTES, represents a marker associated with monocyte‐predominant engraftment. There is close association between the prophylactic administration of defibrotide, a powerful endothelial protector, and the incidence of vascular endothelial syndromes ( P  < 0.0001). Given the high cost of defibrotide, selective prophylaxis may be considered for patients with extremely high values of RANTES or with monocyte engraftment.